Localization and tracking of acoustic sources in room environment - Wu, Kai (2017)
This thesis addresses two areas of the acoustic source localization and tracking (ASLT) problem in a room environment, namely, tracking of acoustic sources using multiple omni-directional microphone arrays and DOA estimation of the acoustic sources using a single acoustic vector sensor (AVS). The challenges for the ASLT problem, in both aforementioned applications may include room reverberation, background environmental noise, sound interference, as well as the presence of multiple speakers.